A Tale of Two Synagogues: Culture, Conflict and Consolidation in the Jewish Community of Saint John, 1906-1919 - Chouinard, Craig (Canadian Jewish Studies / Études juives canadiennes, 1994)
The history of the Jewish community in Saint John, New Brunswick has the characteristics of both large and small-town Jewish communities. Saint John paralleled the early Jewish communities of Montreal and Toronto in its formation by English and German communities in the 1850s. Cultural and socioeconomic divisions between the Anglophile old community and the later immigrants from Eastern Europe resulted in a split into two synagogues in 1906, as was also the case in the larger communities. Economic changes resulted in Saint John’s decline as a major industrial centre by 1914. This decline, combined with closer cooperation between the two Jewish groups, produced a sense of community leading to the reunification of the synagogue in 1919-20, thus reverting to the profile of the one-synagogue smaller communities.